Postoperative tonsil/adenoidectomy bleeding management in patients with diagnosed bleeding disorders. Issue 4 (10th June 2021) - Pai, Kavya; Desai, Harsh; Stein, Dagmar; Cole, Stephanie
Abstract: Objective: Tonsil/adenoidectomy (T/A) is a commonly performed procedure with an average post‐tonsillectomy bleed (PTB) rate between 3 and 5%. Patients with bleeding disorders (BDs) are believed to have an increased risk of PTB. We hypothesize that our medical management of BD patients using a combination of DDAVP/antifibrinolytic agents has a similar PTB rate to control patients. This study suggests a standardized protocol for patients with BDs to avoid PTB. Methods: A retrospective cohort study was completed for patients with BD who underwent tonsillectomy or T/A at Promedica Toledo or Flower Hospital between 2013 and 2020. Exclusion criteria included incomplete records, diagnosis of BD after surgery, and inability to find age and sex matched control. We defined the control group as patients who underwent T/A without BD. The following variables were collected: age, sex, medical history, BD severity, medications, type of surgery, indication for surgery, estimated blood loss (EBL), pre/postoperative medications, PTB status, and post‐PTB intervention. Results: A total of 164 patient charts were reviewed. There were 82 patients in both cohorts. The BDs represented were platelet function disorder (80.5%), von Willebrand disease (14.6%), and others such as Factor VII and IX deficiency (4.9%). Of the BD patients included, 13.4% had severe disease. There was no significant difference between the age, sex, EBL, and PTB rates. Of the 8 BD patients with PTB, 62% bled 9‐10 days postoperatively and none had severe disease. Conclusion: Our protocol to prevent PTB in patients with BDs produced similar bleed rates to control patients in this study. Further studies are required to assess postoperative length of antifibrinolytic treatment in BD patients. Level of Evidence: III.